Legal Protection Against Auction Prices of Goods Through Instagram in Review of Law Number 8 of 1999 concerning Consumer Protection of Goods and Services - Pulumoduyo, Anggun; Abdussamad, Zamroni; Elfikri, Nurul Fazri (Universitas Negeri Gorontalo, 2024)
the purpose of this research is to find out the legal protection of auction prices of goods through Instagram in review of law number 8 of 1999 concerning consumer protection of goods and services. The research method used in this research is normative research method with qualitative approach. The results of this study Selling or conducting auction activities through social media instagram is not legal because there are no regulations governing and not in accordance with the regulations for the implementation of auctions in Indonesia. Whether through class I auction officials or class II auction officials who do not use the auction hall remains invalid. If this phenomenon occurs, there is a risk, if the loss is no legal protection because the auction via social media instagram does not provide legal certainty. In the Minister of Finance Regulation No. 213 / PMK.06 / 2020 concerning Guidelines for the Implementation of Auctions, there is no legal protection that can be given to Instagram auction accounts. This case the perpetrator clearly violates consumer rights, one of which is stated in Article 4 of the Consumer Protection Law